Pandemics, global risks and adaptation: Challenges for a changing world - Wellyngton Silva de Amorim; José Baltazar Salgueirinho Osório de Andrade Guerra (Research in Globalization, 2020)
Uncertainty, insecurity and complexity are some of the terms defining, now and in the future, the development process of the human species on planet Earth. In order to minimize the impact of these challenges on our lives, we need data, studies and directives which allow us to create resilience and adapting strategies over time. However essential those actions may be, we constantly fail in preventing risks. In this sense, the present critical review aims to discuss the impacts originated in the new (COVID-19) pandemic and, simultaneously, the changes caused by this event within the international scenario.
Keywords: 330; COVID-19; Pandemics; Risk